Desempenho reprodutivo e expressão de genes em fêmeas de Penaeus vannamei (Boone, 1931) alimentadas com óleo de Cocos nucifera (Linnaeus, 1753) como aditivo alimentar - Freitas, Juliana Oliveira de (2024)
The marine shrimp Penaeus vannamei is the most cultivated crustacean species globally. The reproduction of marine shrimp in captivity takes place in specialized laboratories, and at this stage, nutritional factors play a crucial role in the gonadal development, fertility and quality of the offspring of shrimp breeders. For this reason, they are kept on a different diet. Given the increased needs for lipids in the reproductive phase, the use of oils of vegetable origin as a food additive incorporated into the feed represents an alternative. The present study set out to evaluate the reproductive performance and gene expression in P. vannamei females fed a diet using coconut oil as an additive. To this end, a three-month experiment was conducted in the maturation sector of a shrimp producing company. A total of 840 animals were divided into six tanks, which comprised two treatments: control and oil. Each treatment had 420 animals, distributed in three tanks, in which families were formed, with 70 males and 70 females per tank. The shrimp were fed daily with squid, shellfish and food, differing from the oil treatment for the control only by adding coconut oil (Cocos nucifera) to the food, at a concentration of 2.5%. From the reproductive performance data collected daily, it was found that, with the exception of the number of daily eggs and abortions, which did not differ between treatments, in all other parameters analyzed (copulation rates, spawning, hatchings, number of nauplii), females fed diet supplemented with coconut oil showed higher values than the control. Regarding hepatosomatic indices, no significant differences were recorded. In terms of gonadosomatic indexes, only in the second month of production, the index was higher for females in the group fed with food supplemented with coconut oil. The total hemocyte count in the oil treatment was 1.7 times higher than in the control. Histological analysis of the gonads revealed a 1.3 times higher percentage of mature or maturing females when fed a diet supplemented with coconut oil. Regarding the other tissues analyzed (intestine and hepatopancreas), no significant differences were noted. Among the genes analyzed (Hsp70, proPO, SOD, Lipase, Trypsin, vtg, vtgr, mprg), with the exception of lipase, which was not detected in the ovaries, and the vitellogenin receptor, which did not differ in the same tissue, all the others were regulated by coconut oil supplementation. The results obtained confirm the hypothesis that coconut oil added to the feed supplied to breeding females of P. vannamei confers benefits related to reproduction, favoring gonadal development and resulting in a greater number of nauplii. Even greater weight gain was recorded in animals fed food supplemented with coconut oil.